Telehealth Use in a Rural State: A Mixed‐Methods Study Using Maine's All‐Payer Claims Database. Issue 4 (21st October 2020) - Jonk, Yvonne C.; Burgess, Amanda; Williamson, Martha Elbaum; Thayer, Deborah; MacKenzie, Jennifer; McGuire, Catherine; Fox, Kimberley; Coburn, Andrew F.
Abstract: Purpose: This study assesses trends in telehealth use in Maine—a rural state with comprehensive telehealth policies—across payers, services, and rurality, and identifies barriers and facilitators to the adoption and use of telehealth services. Methods: Using a mixed‐methods approach, researchers analyzed data from Maine's All Payer Claims Database (2008‐2016) and key informant interviews with health care organization leaders to examine telehealth use and explore factors impacting telehealth adoption and implementation. Findings: Despite a 14‐fold increase in the use of telehealth over the 9‐year study period, use remains low—0.28% of individuals used telehealth services in 2016 compared with 0.02% in 2008. Services provided via telehealth varied by rurality; speech language pathology (SLP) was the most common type of service among rural residents, while psychiatric services were most common among urban residents. Medicaid was the primary payer for over 70% of telehealth claims in both rural and urban areas of the state, driving the increase of telehealth claims over time. Issues challenging organizations seeking to deploy telehealth included provider resistance, staff turnover, provider shortages, and lack of broadband. Key informants identified inadequate and inconsistent reimbursement as barriers to comprehensive, systematic billing for telehealth services, resulting in underrepresentation of telehealth services in claims data. Conclusions: Claims covered by Medicaid account for much of the observed expansion of telehealth use in Maine. Telehealth appears to be improving access to behavioral health and SLP services. Provider shortages, broadband, and Medicare and commercial coverage policies limit the use of telehealth services in rural areas.